Islamic Boarding School Education Management in Forming the Independence of Students - Ahyar Ahmad Sirojudin; Achmad Sanusi; Abin Syamsudin; Hanafiah (Journal of Islamicate Studies, 2022)
This topic was raised because the management of Islamic boarding schools in shaping the independence of students is very much needed. Santri in Islamic boarding schools are given the transfer of knowledge, values and life skills. Armed with expertise, when students are in the community, they will not be confused about getting a job. The purpose of this study was to observe and study how the real activities at Pondok Pesantren Al-Ittifaq Ciwidey Bandung on attitudes, skills and independence. With the management of Islamic boarding schools, students can determine business opportunities and are given knowledge about the methods or methods developed by the Prophet Muhammad. The value of honesty through what it is, what it is and objectively affects the attitudes and behavior of the students to be honest, not manipulative, especially in entrepreneurship. Obstacles and opportunities are encountered in the process, but all stakeholders strengthen each other to survive, focus on goals and seek problem solving. Existing opportunities are used as well as possible to create independent students. This is taken into consideration considering that it is not possible for students who graduate from Islamic boarding schools to become kiai as a whole, and when entering the world of work today it is very difficult to get a job without life skills. Pondok Pesantren Al-Ittifaq Ciwidey Bandung really hopes that with the provision of life skills, students will be able to create their own jobs without depending on others.